Behavioral Effects of Early Focal Brain Damage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Thirty-nine children, 4-15 years of age, were evaluated using the Achenbach Child Behavior Checklist parent questionnaire to assess behavioral or emotional problems resulting from pre- or perinatal unilateral brain damage, in a study at UCSD School of Medicine, La Jolla, CA.